Prolonged Calorie Restriction Downregulates Skeletal Muscle mTORC1 Signaling Independent of Dietary Protein Intake and Associated microRNA Expression - Margolis, Lee M.; Rivas, Donato A.; Berrone, Maria; Ezzyat, Yassine; Young, Andrew J.; McClung, James P.; Fielding, Roger A.; Pasiakos, Stefan M. (Frontiers in Physiology, 2016)
Short-term (5-10 days) calorie restriction (CR) downregulates muscle protein synthesis, with consumption of a high protein-based diet attenuating this decline. Benefit of increase protein intake is believed to be due to maintenance of amino acid-mediated anabolic signaling through the mechanistic target of rapamycin complex 1 (mTORC1), however, there is limited evidence to support this contention. The purpose of this investigation was to determine the effects of prolonged CR and high protein diets on skeletal muscle mTORC1 signaling and expression of associated microRNA (miR). 12-wk old male Sprague Dawley rats consumed ad libitum (AL) or calorie restricted (CR; 40%) adequate (10%, AIN-93M) or high (32%) protein milk-based diets for 16 weeks. Body composition was determined using dual energy X-ray absorptiometry and muscle protein content was calculated from muscle homogenate protein concentrations expressed relative to fat-free mass to estimate protein content. Western blot and RT-qPCR were used to determine mTORC1 signaling and mRNA and miR expression in fasted mixed gastrocnemius. Independent of dietary protein intake, muscle protein content was 38% lower (P < 0.05) in CR compared to AL. Phosphorylation and total Akt, mTOR, rpS6 and p70S6K were lower (P < 0.05) in CR versus AL, and total rpS6 was associated with muscle protein content (r = 0.64, r2 = 0.36). Skeletal muscle miR expression was not altered by either energy or protein intake. This study provides evidence that chronic CR attenuates muscle protein content by downregulating mTORC1 signaling. This response is independent of skeletal muscle miR and dietary protein.